2018
DOI: 10.1038/s41598-018-35967-3
|View full text |Cite
|
Sign up to set email alerts
|

Gender-specific discrepancy in subjective global assessment for mortality in hemodialysis patients

Abstract: Although subjective global assessment (SGA) is a widely used representative tool for nutritional investigations even among dialysis patients, no studies have examined gender-specific differences in the ability of SGA to predict mortality in hemodialysis (HD) patients. A total of 2,798 dialysis patients were enrolled from clinical research center for end-stage renal disease (CRC for ESRD) between 2009 and 2015. The cohort was divided into two groups based on nutritional status as evaluated by SGA: ‘good nutriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…This could explain the lower Hb levels in the incident HD group, with consequent more need for erythropoietin therapy to correct the anemia and try to reach target Hb level. In harmony with these data, many previous studies reported significantly lower blood hemoglobin, and serum albumin, creatinine, and phosphorus levels in the incident than in the prevalent HD patients [4,18,19].…”
Section: Discussionsupporting
confidence: 63%
“…This could explain the lower Hb levels in the incident HD group, with consequent more need for erythropoietin therapy to correct the anemia and try to reach target Hb level. In harmony with these data, many previous studies reported significantly lower blood hemoglobin, and serum albumin, creatinine, and phosphorus levels in the incident than in the prevalent HD patients [4,18,19].…”
Section: Discussionsupporting
confidence: 63%
“…In this study, analysis of the sex interaction showed that the risk of all-cause death associated with BMI was lower in male patients on HD than in female patients on HD. Previous studies from the present Korean kidney failure cohort have reported that BMI or subjective global assessment (SGA) could be useful for predicting mortality in male patients on HD but not in female patients on HD 21,22 . A greater protective effect www.nature.com/scientificreports/ of higher BMI on survival in male patients on dialysis than female patients on dialysis could be explained by higher skeletal muscle mass and reduced fat mass associated with sex hormones in males 23 and a sex-specific association of skeletal muscles mass and arterial stiffness in dialysis patients 24 .…”
Section: Discussionmentioning
confidence: 90%
“…A possible explanation could be the gender-specific discrepancy that may exist in the association between SGA and mortality. Recently, Ko et al [27] reported that a mortality risk of 'mild-to-severe malnutrition' evaluated by SGA was observed in male patients but not in female patients. In addition, results from a number of epidemiologic studies with large cohorts of HD patients indicated an 'obesity paradox', suggesting that obesity was associated with better survival [28].…”
Section: Discussionmentioning
confidence: 99%